Meningkatkan Pendapatan UMKM Fashion Melalui Literasi Digital - Siti Asriah Immawati; Rosyid Rosyid; M.Imam Muttaqijn (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This Community Service (PKM) was held in Cibodas Village, Cibodas District, Tangerang City. The methods used by the service team are field observation, training and mentoring. The implementation of this PKM aims to provide knowledge about digital literacy to MSME players through training and mentoring for fashion MSME players. A total of 32 fashion MSME players participated in training and mentoring, with different times and places. The results of training and mentoring obtained from the results of the assessment carried out on MSME actors found that the value obtained was 37%, so that MSME actors were sufficient in mastering digital transformation. The above states that the duties of training and mentoring MSMEs have not been said to be good in carrying out their duties and have not had a better impact on MSME actors and the development of MSMEs in mastering digital literacy. Most of the levels of mastery of digital literacy of MSME actors are still in the medium category. So that the income earned by MSME actors is still relatively low.